(untitled) (The Review of Diabetic Studies, 2025)
Oral diseases (dental caries, periodontal disease, oral cancers) remain highly prevalent in Saudi Arabia and impose a substantial health and economic burden. Effective prevention requires integrated public-health strategies that combine clinical dental practice, health informatics, nursing and allied-health support, and public health leadership. This paper reviews the burden of oral disease in Saudi Arabia, describes the current policy environment, and proposes a multidisciplinary model—detailing roles for dentists (general and specialist), specialist health informatics professionals, nursing technicians, and public-health practitioners—to strengthen surveillance, prevention, and care delivery. Key interventions include school-based prevention and fluoride programs, electronic dental records (EDRs) integrated with national health information systems, tele-dentistry, training nursing staff for oral screening and preventive counseling, and targeted policies (sugar taxes, population fluoridation where appropriate). The recommendations align with Saudi Vision 2030 and ongoing Ministry of Health (MOH) initiatives to prioritize preventive care and digital transformation.